Haploidentical transplantation combined with mesenchymal stem cells co-infusion improves survival in severe aplastic anemia: a single-center retrospective study - Tan, Zhengwei; Le, Miaoya; Zhu, Ningning; Liu, Jingjing; Zhao, Yuechao; Hu, Huijin; Yu, Qinghong; Zhang, Yu; Wu, Liqiang; Hu, Tonglin; Wu, Dijiong; Ye, Baodong; et al. (Frontiers in Medicine, 2025)
BackgroundHaploidentical hematopoietic stem cell transplantation (HID-HSCT) serves as an alternative treatment for severe aplastic anemia (SAA) patients lacking a suitable HLA-identical sibling donor. Compared to HLA-matched HSCT, HID-HSCT has higher rates of graft failure (GF) and graft-versus-host disease (GVHD). Recent studies suggest promising clinical outcomes when Mesenchymal stem cells (MSCs) are combined with HID-HSCT for SAA treatment.MethodsThis study retrospectively analyzed clinical data from 190 SAA patients who underwent HID-HSCT with or without MSCs co-infusion. Patients were divided into two groups: the HID group (100 patients receiving only HID-HSCT) and the HID+MSC group (90 patients receiving HID-HSCT combined with MSC co-infusion).ResultsThe analysis revealed that the HID+MSC group had a significantly higher 5-year overall survival rate compared to the HID group (86.6% vs. 75.0%, p = 0.036) and a significantly improved GRFS rate (76.6% vs. 64.0%, p = 0.048). While MSCs co-infusion did not significantly reduce the incidence of aGVHD or cGVHD, a downward trend was observed, particularly for cGVHD (16.6% vs. 26.0%). Both groups showed high cumulative engraftment rates for NE and PLT within 28 days post-transplant, with no significant differences. Regarding viral reactivation, EBV and CMV reactivation rates were similar between the two groups, though four patients in the HID group developed EBV-associated PTLD.ConclusionThis study demonstrates that combining HID-HSCT with MSCs co-infusion is a safe and effective therapeutic strategy that significantly improves survival rates and quality of life in SAA patients.